Prospective Validation of Computed Tomography to Identify Patients at High Risk for Stroke After Transient Ischemic Attack or Minor Stroke. Issue 4 (13th February 2023) - Ferguson, Emma; Yadav, Krishan; Sharma, Mukul; Sivilotti, Marco L.A.; Émond, Marcel; Stiell, Ian G.; Stotts, Grant; Lee, Jacques S.; Worster, Andrew; Morris, Judy; Cheung, Ka Wai; Jin, Albert Y.; et al.
Abstract : Background: Computed tomography (CT) findings of acute and chronic ischemia are associated with subsequent stroke risk in patients with transient ischemic attack. We sought to validate these associations in a large prospective cohort of patients with transient ischemic attack or minor stroke. Methods: This prospective cohort study enrolled emergency department patients from 13 hospitals with transient ischemic attack who had CT imaging. Primary outcome was stroke within 90 days. Secondary outcomes were stroke within 2 or 7 days. CT findings were abstracted from radiology reports and classified for the presence of acute ischemia, chronic ischemia, or microangiopathy. Multivariable logistic regression was used to test associations with primary and secondary end points. Results: From 8670 prospectively enrolled patients between May 2010 and May 2017, 8382 had a CT within 24 hours. From this total population, 4547 (54%) patients had evidence of acute ischemia, chronic ischemia, or microangiopathy on CT, of whom 175 had a subsequent stroke within 90 days (3.8% subsequent stroke rate; adjusted odds ratio [aOR], 2.33 [95% CI, 1.62–3.36]). This was in comparison to those with CT imaging without ischemia. Findings associated with an increased risk of stroke at 90 days were isolated acute ischemia (6.0%; aOR, 2.42 [95% CI, 1.03–5.66]), acute ischemia with microangiopathy (10.7%; aOR, 3.34 [95% CI, 1.57–7.14]), chronic ischemia with microangiopathy (5.2%; aOR, 1.83 [95% CI, 1.34–2.50]), and acute ischemia with chronic ischemia and microangiopathy (10.9%; aOR, 3.49 [95% CI, 1.54–7.91]). Acute ischemia with chronic ischemia and microangiopathy were most strongly associated with subsequent stroke within 2 days (aOR, 4.36 [95% CI, 1.31–14.54]) and 7 days (aOR, 4.50 [95% CI, 1.73–11.69]). Conclusions: In patients with transient ischemic attack or minor stroke, CT evidence of acute ischemia with chronic ischemia or microangiopathy significantly increases the risk of subsequent stroke within 90 days of index visit. The combination of all 3 findings results in the greatest early risk.